PENGARUH PERKUATAN MORTAR JAKET DENGAN VARIASI JARAK SENGKANG BAMBU PADA KOLOM BETON BERTULANG - Muhammad Ainur Rofiq; Christin Remayanti Nainggolan; Ari Wibowo; Indradi Wijatmiko (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
A building consists of several structural elements, one of them is a column that has the function to distribute the entire load of the building towards the foundation. If in the working process is done poorly, the column structure will fail. In addition, the structure of the building that has been established is sometimes not function appropriately based on the initial plan, so the load that works on the structure of the building can exceed limits that are previously calculated. Then, the reinforcement of the column is required to be functioned according to the previous planning. In this case, we use the retrofit column code A.5 and B.5 is a retrofit column that uses 4 pieces and 8 pieces of bamboo longitudinal with a size of 10 x 10 mm and 10 x 5 mm with a distance between 7 cm transversal reinforcement, compared to a retrofit column code A.6 and B.6 is a retrofit column that uses longitudinal reinforcement of bamboo as many as 4 pieces and 8 pieces with a size of 10 x 10 mm and 10 x 5 mm with a distance between transversal reinforcement 11 cm. The column was tested by using a compression test machine to obtain the value of the compressive force and dial gauge to obtain the deflection value. Testing of compressive strength was not carried out in the initial column, but only in the retrofit column. The results of the study between variations of A5 and A6 showed that variations in A5 had an increase in the maximum compressive force of 61.78% while variations in A6 increased by 59.86%, it is concluded that A5 was more effective than A6. Whereas for the research between variations of B5 and B6 it was found that variations in B5 had an increased maximum in compressive force of 48,51 %, it is concluded that B5 was more effective than B6.